Current Trends, Dilemmas and Future Directions in Neuropedagogy in the Field of Early Childhood (Képzés és Gyakorlat : Neveléstudományi folyóirat, 2018)
During the past 25 years, research on brain structure and function has expanded our understanding of the relationship between brain development and learning. This field of study is referred to with several terms such as neuroeducation, neuropedagogy, and Mind, Brain and Education. Although a strong interest in neuroeducation is present among researchers and teachers, often misleading recommendations from neuroscience research are made for classrooms. This article provides an overview of neuroeducational research studies in early childhood education to demonstrate how this field of study impacts teachers’ and parents’ understanding of best practices and optimal development. Also, to address the concern of the valid and reliable research in neuroeducation, we outline the principles of neuroeducational research based on Nouri (2016), and propose directions for future research.